Efektifitas Strategi Promosi Kripik Singkong Barokah terhadap Hasil Penjualan di Era Pandemi Covid 19 - Solihin, Amil; Rasyidi, Ahmad Hafas; Sari, Lisma Dian Kartika (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
Promotional strategy is a strategy used by companies producing goods or services to be launched into the market commercially. Marketing strategy is the determination of policies and plans, goals and objectives that are carried out to achieve the expected final results by researching needs and consumers, producing goods and services, determining price levels, promoting products and distributing products to consumers. The purpose of this study was to determine the promotion strategy of cassava chips on sales results in the era of the COVID 19 pandemic. The data collection techniques used were observation, interviews, and documentation. Thus, the sales results increased in 2019 by Rp 3.257.500 while in 2020 the sales results were Rp 2.858.000 and finally in 2021 the nominal value was Rp 20.835.000